2013
DOI: 10.1371/journal.pone.0068161
|View full text |Cite
|
Sign up to set email alerts
|

Development of Low Phytate Rice by RNAi Mediated Seed-Specific Silencing of Inositol 1,3,4,5,6-Pentakisphosphate 2-Kinase Gene (IPK1)

Abstract: Phytic acid (InsP6) is considered to be the major source of phosphorus and inositol phosphates in most cereal grains. However, InsP6 is not utilized efficiently by monogastric animals due to lack of phytase enzyme. Furthermore, due to its ability to chelate mineral cations, phytic acid is considered to be an antinutrient that renders these minerals unavailable for absorption. In view of these facts, reducing the phytic acid content in cereal grains is a desired goal for the genetic improvement of several crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 56 publications
7
82
0
1
Order By: Relevance
“…The rice IPKI gene (Os04g0661200) is highly expressed in developing grain and activation or suppression of this gene may result in alteration of PA biosynthesis and change in total phosphorus content in rice seeds. Ali et al () developed low phytate rice using RNAi‐mediated seed‐specific silencing of IPKI gene, where the transgenic lines showed down‐regulation of IPKI transcripts with significant reduction in PA levels and higher accumulation of minerals in the milled grains. These finding provide evidence that silencing of IPKI gene can mediate a substantial reduction in seed PA levels without hampering the growth and development of rice plants.…”
Section: Resultsmentioning
confidence: 99%
“…The rice IPKI gene (Os04g0661200) is highly expressed in developing grain and activation or suppression of this gene may result in alteration of PA biosynthesis and change in total phosphorus content in rice seeds. Ali et al () developed low phytate rice using RNAi‐mediated seed‐specific silencing of IPKI gene, where the transgenic lines showed down‐regulation of IPKI transcripts with significant reduction in PA levels and higher accumulation of minerals in the milled grains. These finding provide evidence that silencing of IPKI gene can mediate a substantial reduction in seed PA levels without hampering the growth and development of rice plants.…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al (2007) reported that downregulation of MRP4 under embryo-specific promoters resulted in low-phytate maize and soybean without significant effects on seed dry weight and germination rate. Ali et al (2013) also developed low-phytate rice with no apparent developmental defects by seed-specific silencing of IPK1. However, defects in seed weight, germination frequency, and seedling emergence were observed in several other trials, reflecting a role for InsP 6 in seed development (Bilyeu et al, 2008;Kuwano et al, 2009;Li et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we have developed transgenic golden rice with reduced LOX activity by silencing endogenous lipoxygenase gene to reduce co-oxidation of carotenoids using RNAi technology which is very powerful tool for crop improvement (Saurabh et al 2014). The RNAi-mediated gene silencing of lox gene was driven by tissue-specific Oleosin-18 promoter instead of any constitutive promoter to avoid any undesirable and detrimental effects on the plant (Kuwano et al 2009;Ali et al 2013).…”
Section: Discussionmentioning
confidence: 99%